Spectral characteristics of draw-tower step-chirped fiber Bragg gratings. (June 2016) - Idrisov, Ravil F.; Varzhel, Sergey V.; Kulikov, Andrey V.; Meshkovskiy, Igor K.; Rothhardt, Manfred; Becker, Martin; Schuster, Kay; Bartelt, Hartmut
Abstract: This paper presents research results on the spectral properties of step-chirped fiber Bragg grating arrays written during the fiber drawing process into a birefringent optical fiber with an elliptical stress cladding. The dependences of resonance shift of the step-chirped fiber Bragg grating on bending, on applied tensile stress and on temperature have been investigated. A usage of such step-chirped fiber Bragg gratings in fiber-optic sensing elements creation has been considered. Highlights: Draw-tower step-chirped fiber Bragg grating arrays were written. Draw-tower step-chirped fiber Bragg gratings bandwidth of 0.5 nm was achieved. Obtained gratings can operate properly as a part of a phase interferometric sensor.